1976
DOI: 10.1111/j.1432-1033.1976.tb10192.x
|View full text |Cite
|
Sign up to set email alerts
|

A Calorimetric Study of the CO Bohr Effect of Monomeric Haemoglobins

Abstract: A calorimetric study has been made of the heats of CO reaction with the monomeric haemoglobins of Chironornus thummi thummi I11 and IV as a function of pH. The number of Bohr protons released at pH 7.1 was determined from heats of reaction in different buffers as 0.19 and 0.31 mol H+/mol CO for haemoglobin I11 and IV respectively. The heat of the Bohr ionization process was found to be 6 and 8 kcal/mol H' (25 and 34 kJ/mol) for the haemoglobins 111 and IV. These values are consistent with values found for hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…Solution 'H-NMR studies of the cyanomet form of C. thummi thummi Hbs have shown that the allosteric transition can be detected both in the titration of a His side chain, which is the site of the Bohr proton [5], and in the hyperfine shifts for the heme in this low-spin ferric form [12, 131. One property that makes the C. thummi thummi Hbs poor candidates for structural studies is that they exhibit heterogeneities that plague both solution and crystal structures [S, 14,151.…”
mentioning
confidence: 99%
“…Solution 'H-NMR studies of the cyanomet form of C. thummi thummi Hbs have shown that the allosteric transition can be detected both in the titration of a His side chain, which is the site of the Bohr proton [5], and in the hyperfine shifts for the heme in this low-spin ferric form [12, 131. One property that makes the C. thummi thummi Hbs poor candidates for structural studies is that they exhibit heterogeneities that plague both solution and crystal structures [S, 14,151.…”
mentioning
confidence: 99%
“…405 (12) 405 (9) 405 (9) 405 ( EPR (electron paramagnetic resonance spectroscopy) data [31,43]. The m(Fe-His) mode of the natural abundance and d 12 -labeled deoxy meso-a and -b subunits is observed at 222 and 225 cm À1 , respectively, i.e.…”
Section: (5)mentioning
confidence: 99%
“…by 15 cm À1 , upon the d 12 substitution (Fig. 2) is assigned to a C b -propionate bending mode [20,14,25,43], one of the most characteristic heme modes. Almost the same frequency of this mode is observed in the deoxy mesoHb of CTT [5].…”
Section: (5)mentioning
confidence: 99%
“…We have chosen this protein because it is unique in many respects. Its ligand affinity increases with pH (Gersonde et al, 1986), and a pronounced conformational change accompanies the transition from the low-affinity to the high-affinity state (Gersonde et al, 1976;La Mar et al, 1978;Peyton et al, 1991), such that soaking crystals of CTT-Hb-III obtained at acidic pH in alkaline buffer causes them to crack (Steigemann and Weber, 1979). Thus, despite its relatively simple monomeric structure, CTT-Hb-III undergoes pH-induced conformational transitions and is therefore particularly well suited to pinpointing possible relationships between protein dynamics and functional complexity.…”
Section: Introductionmentioning
confidence: 99%